2014
DOI: 10.1002/lary.24930
|View full text |Cite
|
Sign up to set email alerts
|

Admission after sleep surgery is unnecessary in patients without cardiovascular disease

Abstract: 2B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Two studies reported no ITU admissions ( n = 83) among inpatients 12,13,15 of which one monitored all inpatients with continuous pulse oximetry overnight 15 . All the inpatients of two studies ( n = 323) were admitted to the high dependency unit or a similar ward set‐up with a higher nurse to patient ratio and continuous pulse oximetry monitoring as a routine precaution 8,16 . Seventy five out of 216 (34.7%) inpatients of the remaining two studies were admitted to intensive care unit although the criteria for this was unclear and the level of intervention each patient received was unclear (whether it is for monitoring or if patients were kept intubated and ventilated) 7,11 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported no ITU admissions ( n = 83) among inpatients 12,13,15 of which one monitored all inpatients with continuous pulse oximetry overnight 15 . All the inpatients of two studies ( n = 323) were admitted to the high dependency unit or a similar ward set‐up with a higher nurse to patient ratio and continuous pulse oximetry monitoring as a routine precaution 8,16 . Seventy five out of 216 (34.7%) inpatients of the remaining two studies were admitted to intensive care unit although the criteria for this was unclear and the level of intervention each patient received was unclear (whether it is for monitoring or if patients were kept intubated and ventilated) 7,11 …”
Section: Resultsmentioning
confidence: 99%
“…Of these procedures, the majority (57.2%) were performed in hospital‐based ambulatory surgery centers . Otolaryngology has increased the amount of outpatient procedures performed annually over the past 20 years, and data supports outpatient management of a wide range of otolaryngologic issues including pediatric disease, airway pathology, and sleep disorders . Further review of the NHSR data revealed that sinonasal procedures accounted for 600,000 ambulatory surgical visits in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo realizado por Rotenberg et al (2015) os pacientes foram categorizados em dois tipos: com alta hospitalar no mesmo dia, com 78% (n=39) e admissão hospitalar 22% (n=11), referentes a Apneia Obstrutiva do Sono (AOS), para os pacientes que receberam alta, não houve complicações. Para os pacientes admitidos, não teve complicações relacionadas com AOS enquanto internado no hospital.…”
Section: Complicações Pós-operatóriasunclassified